1995
DOI: 10.1063/1.470633
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic structure of the cyclopentadienyl radical and its nonrigid van der Waals cluster with nitrogen

Abstract: Fluorescence excitation and two color mass resolved excitation spectroscopy are employed to study the D 1 (2 A 2 Љ)←D 0 (2 E 1 Љ) vibronic transitions of the cyclopentadienyl radical ͑cpd͒ and its van der Waals cluster with nitrogen. The radical is created by photolysis of the cyclopentadiene dimer and cooled by expansion from a supersonic nozzle. The cpd͑N 2 ͒ 1 cluster is generated in this cooling process. Mass resolved excitation spectra of cpd are obtained for the first 1200 cm Ϫ1 of the D 1 ←D 0 transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…As a test of the method for calculating energy differences, [124] have also optimized the D 5h minimum structure (labeled M(D 2 )) on D 2 ( 2 A' 2 ). The value for the 0-0 electronic transition was calculated as 86.6 kcal mol -1 , in good agreement with the experimental value of 84.6 kcal mol -1 (29,573 cm -1 ) [146,147]. Table 1 of ref.…”
Section: Structure and Nuclear Dynamics In Free Radicals: The Jahn-tesupporting
confidence: 83%
“…As a test of the method for calculating energy differences, [124] have also optimized the D 5h minimum structure (labeled M(D 2 )) on D 2 ( 2 A' 2 ). The value for the 0-0 electronic transition was calculated as 86.6 kcal mol -1 , in good agreement with the experimental value of 84.6 kcal mol -1 (29,573 cm -1 ) [146,147]. Table 1 of ref.…”
Section: Structure and Nuclear Dynamics In Free Radicals: The Jahn-tesupporting
confidence: 83%
“…[68] Experimental studies of electronic transitions in complexes involving radicals are even scarcer.S un and Bernstein have compared the interaction of benzene and benzyl and cyclopentadienyl radicals with an itrogen molecule. [69] They found that the origin of the first electronic transition of thesem olecules in the complexes could be either blue-or red-shifted compared with the monomers. Thec loseste xample to our system seems to be the complexes of NCO radical with Ar,N 2 , CH 4 ,a nd CF 4 .…”
Section: Discussionmentioning
confidence: 99%
“…As is described in previous work, 31,32 the experiment is carried out in a stainless steel vacuum chamber at a pressure of ca. 10 Ϫ4 Torr.…”
Section: A Experimentsmentioning
confidence: 99%
“…Cluster geometry and binding energy are obtained employing an atom-atom potential energy calculation. 31,32 All molecules are considered as rigid entities in this calculation. The interaction energy is determined as a sum of various terms: short range repulsion, induction/dispersion, Coulomb, and hydrogen bonding.…”
Section: B Theorymentioning
confidence: 99%